Immuno-positive stained of Ki-67 from formalin-fixed paraffin-embedded serous cystadenoma and serous epithelial ovarian carcinoma specimens / Rima Melati Mat Satar ... [et al.] - Mat Satar, Rima Melati; Bakar, Nor Salmah; Yusof, Hartini; Mustakim, Maimunah (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
A vast archive of biopsy and autopsy specimens processed for histological diagnosis exists in pathology laboratory worldwide has potential value for immunohistochemistry studies associated with protein identification such as Ki-67. Determination of cellular activity has been reported to be of a diagnostic with prognostic value used to estimate the number of proliferating cells in ovarian carcinoma. Ki-67 antigen was found to be a reliable diagnostic marker for estimating the Proliferative Index (PI) of a neoplastic lesion by the Mindbomb E3 ubiquitin protein ligase1 (MIB-1 antibody) using immunohistochemistry. However, there is lack of published studies about Ki-67 from serous epithelial ovarian carcinoma (SEOC) in Malaysia. Thus, the purpose of this study is to identify immuno-positive stained associated with protein expression of Ki-67 from serous cystadenoma and SEOC specimens. 76 FFPE specimens which consist of 36 serous cystadenoma and 40 SEOC samples were sectioned and subjected to immuno-histo staining using monoclonal M1B1 antibody. Immuno-positive stained for Ki-67 was analysed by the blinded consultant pathologist. The results were presented as percentage and mean of Ki-67 labelling index (LI) among the samples studied. Protein positivity of Ki-67 was detected in 49 specimens (64.5%), comprising of 9 serous cystadenoma (11.8%), 15 low-grade SEOC (19.7%), and 25 highgrade SEOC (33.0%). Mean Ki-67 LI was higher in SEOC (42.50±27.07) compared to serous cystadenoma (1.99±3.59), and the difference was statistically significant (p=0.000). This study showed that archive FFPE samples were useful to be used for immunohistochemistry study.